Features of Emotional Intelligence, Empathy and Alexithymia in Persons Dependent on Psychoactive Substances with Different Experiences of Their Use - Yulia A. Kochetova; Irina A. Golovanova; Maria V. Klimakova (Peoples' Friendship University of Russia (RUDN University), 2023)
The research is aimed at identifying the specifics of the components of emotional intelligence (EQ) in persons with different experiences of substance abuse. The study involved 157 respondents aged 35 to 45 years, of whom 111 were dependent on psychoactive substances and 46 never used them. The empirical study was carried out using The Emotional Intelligence Questionnaire (EmIn) by D.V. Lyusin, The Balanced Emotional Empathy Scale (BEES) by A. Mehrabian and N. Epstein, and The Toronto Alexithymia Scale (TAS). Significant differences were found for almost all the variables (except for empathy and the 'intrapersonal management' EQ component) between the group of persons who did not use psychoactive substances and the groups of persons dependent on such substances. The obtained results also make it possible to speak about differences in the correlations between the components of emotional intelligence with each other, as well as with empathy and alexithymia among the groups of subjects with different experiences of substance abuse. In individuals who did not use psychoactive substances, all the components of emotional intelligence are interconnected. In the addicts, as the duration of substance abuse increases, the number of connections between the components of emotional intelligence, both among themselves and with alexithymia, decreases.